2013
DOI: 10.1097/mao.0b013e318298ac96
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Imaging in the Diagnosis and Management of Otosclerosis

Abstract: This systematic review indicates that imaging has a useful role in both the diagnosis and management of otosclerosis, supported principally by Level III/IV evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…The PPV of 100 % is a reliable measure and is in keeping with previous studies [4]. Recent studies [19] have also demonstrated >90 % sensitivity of CT in diagnosing otosclerosis. There remain a small percentage of infra-radiological cases, which can only be confirmed during surgery and this is either due to small submillimetre foci, or due to foci of 'inactive disease', which have the same density as the surrounding bone [20,21].…”
Section: Discussionsupporting
confidence: 65%
“…The PPV of 100 % is a reliable measure and is in keeping with previous studies [4]. Recent studies [19] have also demonstrated >90 % sensitivity of CT in diagnosing otosclerosis. There remain a small percentage of infra-radiological cases, which can only be confirmed during surgery and this is either due to small submillimetre foci, or due to foci of 'inactive disease', which have the same density as the surrounding bone [20,21].…”
Section: Discussionsupporting
confidence: 65%
“…Virk et al reviewed 37 articles and found that imaging has a useful role in both the diagnosis and management of otosclerosis supported by level III/IV evidence, with newer multi-detector scanners demonstrating a sensitivity and specificity in excess of 90% (19). We believe that a preoperative high-resolution CT scan is useful not only to confirm a doubtful diagnosis but also to evaluate the extension of lesions, predict surgical difficulties, and rule out purely cochlear otosclerosis or other diagnoses.…”
Section: Discussionmentioning
confidence: 91%
“…The role of CT scan in otosclerosis continues to be debated even though several recent publications and systematic reviews recommend it as the gold standard for diagnosis (18,19). Virk et al reviewed 37 articles and found that imaging has a useful role in both the diagnosis and management of otosclerosis supported by level III/IV evidence, with newer multi-detector scanners demonstrating a sensitivity and specificity in excess of 90% (19).…”
Section: Discussionmentioning
confidence: 96%
“…It lacks sensitivity as the presence of intraoperative ossification has frequently been reported even in the absence of any ossification on the scan [Castillo et al, 2014] but has high specificity with higher grades of otosclerotic changes on CT [Rotteveel et al, 2004]. However, studies over the last 8 years report high detection rates in excess of 90% for fenestral otosclerosis since the advent of more advanced multidetector scanners and techniques [Virk et al, 2013]. Twelve of our 22 otosclerotic subjects had been implanted before 2010, a fact that could explain why signals of ossification were not observed in some CT images.…”
Section: Findings In Subjects With Otosclerosismentioning
confidence: 96%